Fiscal policies and household consumption during the COVID-19 pandemic: A review of early evidence - Andreas Hackethal; Annika Weber (Leibniz Institute for Financial Research SAFE, 2020)
We review early evidence on how household consumption behavior has evolved over the pandemic and how different groups of households have responded to fiscal stimulus programs. Due to the scarcity of evidence for Europe, our review focuses on evidence from the US. Notwithstanding the institutional and demographic differences, we highlight generalizable findings and challenges to the design of stimulus policies from the pandemic. In conclusion, we identify several open issues for discussion.
Keywords: D14; E21; E62; E71; G51; 330; Household Finance; Consumption; COVID-19; Stimulus